Objective method of forecasting thunderstorms In winter season over Delhi State - KUMAR, SURENDRA (MAUSAM, 1972)
The purpose of this study was to develop an objective aid for forecast1ng of thunderstorms in winter season over Delhi State. Relationship of a number of meteorological parameters to subsequent thunderstorm activity was investigated. The five parameters showing strongest relationship were finally selected and analysis applied to form objective forecast aid. The method was tested on independent data and the results were consistent with those obtained on developmental data.